Assessing population‐level response to interacting temperature and moisture stress. Issue 5 (25th July 2015) - Oke, Tobi A.; Wang, Jian R.
Abstract: Greenhouse experiments have been pivotal to predicting the likely response of tree species to future climate. However, there are some common inadequacies in the inferences derived from many of the studies. Moisture and temperature effects are tightly coupled but in controlled experiments, only a few studies acknowledged the interacting nature of these factors. Furthermore, there is evidence that population‐level plasticity is relevant to plant survival in novel environments. We posit that an inference derived from response to a single climatic factor is likely incomplete and hypothesised that adaptive properties inherent in population‐level plasticity mediate plant growth in novel environments. We tested this hypothesis using a greenhouse experiment involving four populations of white birch ( Betula papyrifera Marsh) grown under two temperatures and two moisture regimes. We examined variations in their photosynthetic rates ( A ), water‐use efficiency (WUE), water potential ( ψ pd ) and stomatal conductance ( g s ). We also investigated variations in their height growths, height relative growth rates ( RGR ht ), and biomass accumulations. Interaction of temperature and moisture was consistently significant for most of the traits. Contrary to expectation, population from cold climate had the highest growth in the high temperature treatments while a coastal population had the highest WUE in low water treatments and also showed greatest decline in growth responses. Some of the results also suggest that there is an overriding effect of phenotypic plasticity over local adaption in white birch. Collectively, the results underscore the growing awareness that populations would likely respond differently in the event of climate change.